2012
DOI: 10.1371/journal.pone.0029208
|View full text |Cite
|
Sign up to set email alerts
|

Largazole and Its Derivatives Selectively Inhibit Ubiquitin Activating Enzyme (E1)

Abstract: Protein ubiquitination plays an important role in the regulation of almost every aspect of eukaryotic cellular function; therefore, its destabilization is often observed in most human diseases and cancers. Consequently, developing inhibitors of the ubiquitination system for the treatment of cancer has been a recent area of interest. Currently, only a few classes of compounds have been discovered to inhibit the ubiquitin-activating enzyme (E1) and only one class is relatively selective in E1 inhibition in cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 45 publications
0
51
0
2
Order By: Relevance
“…PYR-41 inhibiting the ubiquitin-E1 could occur either by Michael addition to the exocyclic double bond or via reaction with the N-aryl bond (Yang et al, 2007). The octanoyl residue is important for the ability of largazole and its derivatives to inhibit E1 activity (Ungermannova et al, 2012). In this study, ellagic acid and tannic acid may covalently modify E1 through nucleophilic attack to react with the active site cysteine of E1.…”
Section: Discussionmentioning
confidence: 94%
“…PYR-41 inhibiting the ubiquitin-E1 could occur either by Michael addition to the exocyclic double bond or via reaction with the N-aryl bond (Yang et al, 2007). The octanoyl residue is important for the ability of largazole and its derivatives to inhibit E1 activity (Ungermannova et al, 2012). In this study, ellagic acid and tannic acid may covalently modify E1 through nucleophilic attack to react with the active site cysteine of E1.…”
Section: Discussionmentioning
confidence: 94%
“…This depsipeptide contains a 4-methylthiazoline fused to a thiazole ring and an octanoic thioester side chain, and is another novel chemical scaffold that may preferentially target cancer cells over normal cells; consequently, largazole is a potentially valuable cancer chemotherapeutic. Largazole potently inhibits class I histone deacetylases (HDACs), and is a novel class of ubiquitin E1 inhibitor (Ungermannova et al, 2012). Due to the intriguing structure and the potential as selective anticancer drug candidate, a great deal of attention has been focused on the synthesis of largazole and its analogs (Li et al, 2011).…”
Section: Ribosomal-and Nonribosomal-derived Peptides: a Virtually Unlmentioning
confidence: 99%
“…In another study by Ghosh and co-workers, largazole was shown to be effective in sensitizing EBV + (Epstein-Barr virus + ) lymphoma cells to the antiherpes viral drug, ganciclovir, at nanomolar concentrations [85]. Recently, Ungermannova and co-workers revealed largazole and related analogues to be novel inhibitors of ubiquitin activating enzyme (E1) and are useful as potential molecular tools for understanding the ubiquitination process [86].…”
Section: Largazolementioning
confidence: 99%